Item Generation and Reduction Toward Developing a Patient-reported Outcome for Pediatric Ulcerative Colitis (TUMMY-UC). Issue 3 (March 2017) - Marcovitch, Liron; Nissan, Anat; Mack, David; Otley, Anthony; Hussey, Seamus; Mclean, Beth; Lewis, Mary; Croft, Nick; Barakat, Farah M.; Griffiths, Anne M.; Turner, Dan
ABSTRACT: Background: The Pediatric Ulcerative Colitis Activity Index (PUCAI) is a noninvasive clinician-based index, which reflects disease severity in pediatric ulcerative colitis (UC) when no endoscopy is performed. Here, we aimed to explore signs and symptoms important to children with UC and their caregivers as the first stage of developing a patient-reported outcome (PRO) measure for pediatric UC (ie, the TUMMY-UC index) to supplement endoscopic assessment. Methods: Concept elicitation qualitative interviews were performed with children who have UC and their caregivers in 6 centers. Items were rank-ordered by the interviewees according to the frequency of endorsement and importance, graded on a 1 to 5 scale. Results: A total of 46 children (ages 12.5 ± 3.3 years, range 7–18, 48% boys, 83% with pancolitis, 24% with moderate–severe disease) and 33 caregivers were interviewed (ie, 79 interviews). The following items were identified by the children, in decreasing order of weights: abdominal pain (importance × frequency weight 3.9), rectal bleeding (3.6), stool frequency (3.0), stool consistency (3.0), general well-being/fatigue (2.9), urgency (1.9), and nocturnal stools (1.6). Two other items were scored lower: lack of appetite (1.1) and weight loss (0.6). Children 13 to 18 years comprehended adult vocabulary, children 8 to 12 years comprehended simple vocabulary, and younger children had poor understanding in completing the questions. Conclusions: In this first stage of the TUMMY-UC development, items were generated and ranked by input from patients. These items are now being explored for optimal vocabulary and response options. The TUMMY-UC will supplement the PUCAI in clinical trial outcome assessment. Abstract : Supplemental Digital Content is available in the text